2017
DOI: 10.3892/etm.2017.5222
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of arachidonoylethanolamide levels by activation of the endocannabinoid system protects against colitis and ameliorates remote organ lesions in mice

Abstract: Abstract. The endocannabinoid system (ECS) is a potential pharmaceutical target for the treatment of inflammatory bowel diseases (IBDs). The aim of this study was to explore the effects of activation of the ECS on IBD and the associated neural inflammation-induced disruption of the blood-brain barrier (BBB). In a mouse model of trinitrobenzene sulfonic acid-induced colitis, the inhibition of fatty acid amide hydrolase with URB597 elevated the arachidonoylethanolamide concentration of the colon. Macroscopic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One study has suggested that therapeutic FAAH inhibition may have additional benefits over prophylactic administration, although this remains to be replicated. 98 Despite several studies demonstrating a benefit of FAAH inhibition, findings are not unanimous. One study demonstrated that PF3845 is effective at ameliorating colitis in the TNBS model but not the DSS model.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…One study has suggested that therapeutic FAAH inhibition may have additional benefits over prophylactic administration, although this remains to be replicated. 98 Despite several studies demonstrating a benefit of FAAH inhibition, findings are not unanimous. One study demonstrated that PF3845 is effective at ameliorating colitis in the TNBS model but not the DSS model.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…As global FAAH inhibition is associated with suppression of colonic inflammation [ 89 97 ], we administered the FAAH inhibitor intracerebroventricularly (icv) to be able to establish the importance of central FAAH inhibition on colitis-induced anxiety. Rats underwent intracranial cannulations as previously described [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Endocannabinoids can also display anti-inflammatory effects in different AIDs; however, their pharmacological potential is still debated. The exogenous supplementation of either COX-2 inhibitors [130], cannabinoid receptor agonists [65,66], or endocannabinoid degradation inhibitors [65,[130][131][132] increased the levels of anti-rheumatic N-acylethanolamines. In the same way, in some diseases, the modulation of S1P pathway could be accomplished indirectly and not using exogenous S1P.…”
Section: Anti-inflammatory Lipids and Their Therapeutic Potentialmentioning
confidence: 99%